Research trends for papillary thyroid carcinoma from 2010 to 2019: A systematic review and bibliometrics analysis. Issue 21 (28th May 2021) - Huang, Fengyan; Wang, Lihua; Jia, Hongying
Abstract: Background: Thyroid carcinoma comprises the fastest rising incidence of carcinomas over the past decade. Papillary thyroid carcinoma (PTC) is the most predominant type of thyroid carcinoma. This study aimed to assess the research trends in the field of PTC. Methods: Publications from January 2010 to December 2019 were retrieved from the Web of Science Core Collection database using Thompson Reuters. Searching strategies were determined according to Medical Subject Heading terms. Different kinds of bibliometrics software, such as HistCite and VOSviewer, and online bibliometrics analysis platforms were utilized to evaluate and visualize the results. Results: A total of 8102 publications across 93 countries were identified, with the annual number of publications showing an increasing trend. The United States, China, and South Korea showed their dominant position in PTC publication outputs, H-index, total citations, and international collaborations. Thyroid was the most productive journal. Akira Miyauchi published the most articles, and the most productive institution was Yonsei University . The hotspots keywords proliferation, invasion and metastasis, diagnoses and prognoses, therapeutic resistance, recurrence, and microcarcinomas appeared earlier and were sustained over the last 3 years. Conclusions: This bibliometric study provides a comprehensive analysis delineating the scientific productivity, collaboration, and research hotspots within the PTC field, which will be very helpful when focusing on the direction of research over the next few years.